Pattern of skeletal metastasis in breast cancer patients of northern part of Bangladesh - Rahman, A. M. M. Minhazur; M. Murshed Ali (International Journal of Research in Medical Sciences, 2023)
Background: Breast cancer is the most frequent female cancer, especially in ’developed’ countries. 30-85% of metastatic breast cancer patients will develop bone metastases during the course of the disease. The study was aimed to evaluate the pattern of skeletal metastasis in breast cancer patients with whole body bone scan using 99mTechnetium methyl diphosphonate (99m’Tc-MDP). Methods: This single center based retrospective observational study was conducted among the histopathologically proven breast cancer patients referred to INMAS, Rangpur for 99m’Tc-MDP bone scintigraphy between March 2015 and March 2019. Bone scan was done with SPECT digital dual head gamma camera (Siemens S series) 3 hours after intravenous bolus injection of 20 mci99mI’c-MDP. Results: Out of total 300 patients, 120 (40%) patients were found secondaries in bones. Among them 80(66.7%) had only axial skeletal metastases and 15 (12.5%) had appendicular skeletal metastases. Both axial and appendicle skeletal metastases were found in 25 (20.8%) patients. Conclusion: Thoraco-lumbar spine was the most common site of involvement in our study.